Vergleich von Blutfluß und Benzodiazepin-Rezeptorverteilung bei fokaler Epilepsie: Vorläufige Ergebnisse einer SPECT-Studie - Bartenstein, P.; Ludolph, A.; Schober, O.; Lottes, G.; Böttger, I.; Beer, H.-F. (Nuklearmedizin - NuclearMedicine, 1989)
99mTc-HMPAO-SPECT and SPECT with the 123I-labelled benzodiazepine (Bz) receptor ligand Ro 16-0154 were performed in 10 patients suffering from partial epilepsy, without cerebral lesion in MRT or CT. 2 h p.i. of Ro 16-0154 the distribution of activity correlated with the known distribution of Bz- receptors in the human brain. Perfusion and receptor-binding were found decreased in 7 patients of each study in the suspicious brain-area. 123l-labelled Ro 16-0154 is suitable for Bz-receptor mapping by SPECT. The decrease of Bz-receptor binding in epileptic foci, as described in PET-studies, was also detected by SPECT in 7 of 10 patients.